The award [compact disc, unabridged] : a novel - Steel, Danielle (Brilliance Audio, Inc., 2016)
Gaelle de Barbet is sixteen years old in 1940 when the German army occupies France and frightening changes begin. She is shocked and powerless when French gendarmes take away her closest friend, Rebekah Feldmann, and her family, and send them to a detention camp for deportation to an unknown, ominous fate. The local German military commandant makes Gaelle's family estate outside Lyon into his headquarters. Her father and brother are killed by the Germans; her mother fades away into madness and ill health. Trusted friends and employees become traitors. And by accident, Gaelle begins a perilous journey with the French Resistance, hoping to save lives to make up for the beloved friend she could do nothing to help.